Modulation of TRPV1 on Odontoblast-like Cells Using Capsazepine-Loaded Nanogels - Lilia Jadith Bernal-Cepeda; Ronald Andrés Jiménez; Myriam L. Velandia-Romero; Paola Acosta-Guzmán; Jaime E. Castellanos (MDPI AG, 2024)
The modulation of TRPV1 emerges as a promising strategy for dental pain management. This study aimed to assess TRPV1 modulation in a human odontoblast-like cell model using Capsazepine (CZP) loaded in a nanogel delivery system. Gelatin nanogels, synthesized via the emulsification-gelation technique, were characterized and loaded with the TRPV1 antagonist, CZP. HPLC determined a remarkable 67.5 ± 0.04% CZP loading efficiency, with 71.7% of nanogels falling within the 300-950 nm size range, as evidenced by light microscopy. Moreover, CZP-loaded nanogels had a low cytotoxicity. An FTIR analysis showed no adverse chemical interactions, ensuring stability and active release. When examining biological responses, TRPV1 expression and channel activity were assessed in odontoblast-like cells. On the fifth day post-treatment, cells treated with CZP-loaded nanogels exhibited an increased TRPV1 expression and a reduction in calcium fluxes after agonist stimulus (F/F0 ratio 1.18 ± 0.18), resembling the response in free CZP-treated cells (1.28 ± 0.15). A two-way analysis of variance and the Tukey's test were used to determine statistical significance (p < 0.05). This delivery system, proven to be economical and straightforward, holds promise for dental pain management and potential local use. Local administration minimizes systemic adverse effects, making it a practical solution for releasing molecules in the oral cavity.